Student Worksheet Design using Prompting Model to Facilitate Mathematics Problem Solving Ability - Ufi Lutfiah; Rina Oktaviyanthi; Khotimah Khotimah (IKIP Siliwangi, 2022)
This study aims to determine the feasibility of LKPD teaching materials with the probing prompting learning model to facilitate the mathematical problem solving abilities of junior high school students on the flat-sided building material (cubes and blocks) and to determine student responses to the developed student worksheets (LKPD). This study uses research and development methods with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The results of the research data obtained, and it can be concluded that the student worksheet (LKPD) of the probing prompting model is suitable for use with the results of the material test ( x = 33), mathematics education test ( x = 54), and media expert test ( x = 63). Student responses when viewed based on the results of the overall aspect value of the limited scale test, the value ( x = 45.71) is in the very feasible category. Meanwhile, the students' responses to the wide-scale (field) test based on the overall aspect scored (x =46.81) with a very decent category.